Diabetes the Most Common and Challenging Health Issue of the Modern Life - Md. Tahfizur Rahman; Soma Rani Kolay; Shagufta Nigar (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Diabetes mellitus is a rapidly increasing chronic disease associated with complications resulting in long-term damage and failure of various organ systems. The disorder characterized by hyperglycemia and disturbed metabolism of glucose, fat, and protein. It has emerged as a leading global health problem as the prevalence of Diabetes mellitus is rapidly increasing at epidemic levels throughout the world. Today, diabetes is not the devastating diagnosis it would have been 100 years ago; in fact, it is now a common misconception among the public that diabetes is not a serious disease. In reality, the impact of diabetes is so significant that it is affecting overall life expectancy. The diabetic complications were high among the diabetic patients in TASH. The majority of patients had poor glycemic control. Chronic microvascular complications particularly neuropathy was the most common.